Inovasi Pembuatan Telur Asin Organik untuk Mendukung Pengembangan UMKM Berbasis Potensi Lokal di Kabupaten Kolaka - Asdar Asdar; Putu Sri Dewi; Fatima Fatima; Riana Eka Cahyani; Rina Sardiana Sari; Mustakim Mustakim (Jurnal PKM Manajemen Bisnis, 2026)
Kolaka Regency has considerable potential in developing Micro, Small, and Medium Enterprises (MSMEs) based on local livestock products, particularly salted eggs. However, the utilization of chicken eggs as an alternative raw material and the application of different salting methods have not been widely introduced to the community. This community service activity aimed to introduce the production of organic salted eggs using two methods, namely the brining method and the mud-coating method, by utilizing both duck eggs and commercial chicken eggs. The activity was carried out through preparation of tools and materials, production practice, observation of product quality, packaging, and product introduction as a local MSME innovation. The instruments used included observation sheets and documentation during the implementation process. Data were analyzed descriptively by comparing the implementation process and the resulting products from both methods. The results showed that both methods successfully produced organic salted eggs with good quality, distinctive taste, and attractive appearance. The brining method was easier to apply and produced a more uniform salt distribution, while the mud-coating method provided a more traditional processing technique with satisfactory product quality. This innovation demonstrates that both duck eggs and commercial chicken eggs can be processed into value-added products that have the potential to support local entrepreneurship and improve community income in Kolaka Regency.